2009
DOI: 10.1007/s11104-009-9960-x
|View full text |Cite
|
Sign up to set email alerts
|

High potential, but low actual, glycine uptake of dominant plant species in three Australian land-use types with intermediate N availability

Abstract: The traditional view of the nitrogen (N) cycle has been challenged since the discovery that plants can compete with microbes for low molecular weight (LMW) organic N. Despite a number of studies that have shown LMW organic N uptake by plants, there remains a debate on the overall ecological relevance of LMW organic N uptake by plants across ecosystems with different N availabilities. We here report patterns of glycine N uptake by plants from three different Australian land-use types with intermediate N availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 54 publications
3
14
0
Order By: Relevance
“…Bloom et al 1992;BassiriRad et al 1999). Similarly, rates of NH 4 + and NO 3 − uptake that we measured using the ex situ 15 N tracer method with excised roots (median range 0-0.23 and 0-0.018 μmol N gdw -1 h −1 , respectively) were within the range of rates observed in other studies as well (Kahmen et al 2009). …”
Section: Nh 4 + Vs No 3 − Uptakesupporting
confidence: 87%
See 2 more Smart Citations
“…Bloom et al 1992;BassiriRad et al 1999). Similarly, rates of NH 4 + and NO 3 − uptake that we measured using the ex situ 15 N tracer method with excised roots (median range 0-0.23 and 0-0.018 μmol N gdw -1 h −1 , respectively) were within the range of rates observed in other studies as well (Kahmen et al 2009). …”
Section: Nh 4 + Vs No 3 − Uptakesupporting
confidence: 87%
“…We also observed greater NH 4 + uptake by intact compared with excised roots using the in situ depletion method in those roots where there was net uptake. Root excision causes carbohydrate supply to decrease over time, thus interrupting the active flow of nutrients into the root (Bloom and Caldwell 1988;Aslam et al 1996b;Kahmen et al 2009). Our results comparing uptake by intact vs. excised roots could be attributed to the interacting effects of excision and the duration of time between excision in the field and measurement of N uptake (immediately using the in situ depletion method and up to 24 h using the ex situ 15 N tracer method).…”
Section: Root N Uptake Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, our results confirmed that the inorganic N forms were still the dominant N sources and were considered to be the preferred N forms taken up by higher plants compared with N-derived from glycine when supplied with equal concentrations (Harrison et al 2007;Kahmen et al 2009;Gioseffi et al 2011).…”
Section: Discussionsupporting
confidence: 75%
“…Although many plant species are capable of absorbing low molecular weight organic molecules such as amino acids (Nasholm et al 1998), these labile molecules constitute a small proportion (*1%) of what is actually comprised in the DON pool (Hannam and Prescott 2003). Furthermore, it is likely that heterotrophic microorganisms are better competitors than plant roots for free amino acids in soil solution (Kahmen et al 2009). Thus, it is unlikely that root uptake could alleviate leaching losses of DON to the same extent as NO 3 -or NH 4 ?…”
Section: Discussionmentioning
confidence: 99%